WORK-LIFE BALANCE AND SERVANT LEADERSHIP FOR BETTER ORGANIZATIONAL COMMITMENT OF TOURISM EMPLOYEES: THE ROLE OF AFFECTIVE WELL-BEING AS A MEDIATOR - Purwanti Dyah Pramanik; Myrza Rahmanita (FEB Universitas Sam Ratulangi Manado, 2023)
The United Nations compiled the Sustainable Development Goals 2030, which included providing decent work for humankind, such as facilitating employees with a balance among work, family, and private life. This study aims to analyze the relationship among variables and the role of affective commitment between work-life balance and servant leadership partially on employees' organizational commitment in the tourism business. The study applied a quantitative descriptive approach, involving 82 workers in the tourism businesses in Jakarta who were selected by purposive sampling from January-May 2023. Smart-PLS was employed to analyze the data. The study reported that affective well-being mediates the correlation between work-life balance and servant leadership. The study implies the need to mix human resource management practices to create a positive work environment to strengthen organizational commitment.